أخلاقيات الإعلام الالكتروني في الجزائر بين واقع الممارسة والضوابط القانونية - سناء مجالدي; الوليد رفاس (University of Eloued جامعة الوادي, 2019)
يعتبر الإعلام الالكتروني من بين نتائج التطورات الحاصلة في تكنولوجيا الإعلام والاتصال وظهور الشبكة العنكبوتية العالمية، والتي بقدر ما أحدثت العديد من الممارسات الإيجابية مغيرة نمط حياة المجتمعات وساهمت في التطور والرقي، بقدر ما كانت لها الآثار السلبية على أفراد المجتمع ومصالح الدول بأسرها، لاسيما وأن الإعلام الالكتروني متاح لجميع المواطنين دون استثناء وغير خاضع للرقابة في الجزائر. إن ظهور الإعلام الالكتروني في العقد الأخير أتاح الفرصة للكثيرين (الصحفيون المواطنون) ممن يمارسون مهام مهنة الصحافة، في التحرير ونشر المواضيع والتعليق على الحوادث والوقائع، وكذا إبداء الرأي اتجاه القضايا التي تصنع الحدث، وهذا تحت أسماء مستعارة وفي الكثير من الأحيان لأغراض سلبية على غرار نهش سمعة وصورة الآخرين سواء أفرادا أو جماعات أو مؤسسات، من دون دليل أو بيانات أو وثائق، وذلك تحت حجة حرية التعبير، وهذا أمام غياب قوانين ونصوص تنظيمية صارمة تعاقب المتسبب لأضرار مادية أم معنية للغير. ومن خلال ما سبق، تعالت العديد من الأصوات من أجل إيجاد ميكانيزمات قانونية وأخلاقية واجتماعية للحد من التصرفات اللامسؤولة والممارسات غير الأخلاقية التي كان من وراءها الفاقدون للضمير المهني وهم الفاعلون في ميدان الإعلام الالكتروني. وعليه، سنحاول من خلال هاته الورقة البحثية التعرف على واقع أخلاقيات الإعلام الالكتروني في الجزائر بين واقع الممارسة والضوابط القانونية. Summary Electronic media is one of the results of the development of information and communication technology and the emergence of the World Wide Web (WWW), which, in so far as it brought about many positive practices, changed the lifestyle of societies and contributed to the development and advancement, as it had negative effects on members of society and the interests of the whole country, Especially since electronic media is available to all citizens without exception and is not subject to censorship in Algeria. The emergence of electronic media in the last decade has provided an opportunity for many (citizen journalists) practicing the tasks of the press profession, in editing and publishing topics and comment on incidents and incidents, as well as expressing an opinion on the issues that make the event, and this under the pseudonyms and often for negative purposes Similar to undermining the reputation and image of others, whether individuals, groups or institutions, without evidence, data or documents, under the pretext of freedom of expression, and this in the absence of strict laws and regulatory texts to punish the person causing material or other damages. In the foregoing, many voices have sought to find legal, ethical and social mechanisms to curb irresponsible behavior and unethical practices that have led to the loss of professional conscience and the actors in the field of electronic media. Therefore, we will try through this paper to identify the reality of the ethics of electronic media in Algeria between the reality of practice and legal controls.
الملتقى الدولي حول الإعلام المحلي في الجزائر التحديات المعاصرة ورهانات المستقبل 16/17 أكتوبر 2019 كلية العلوم الاجتماعية والإنسانية – جامعة الشهيد حمه لخضر الوادي
Keywords: الإعلام الالكتروني، الممارسة، الضوابط القانونية; electronic media, practice, legal controls